Google hacks - Calishain, Tara (O'Reilly, 2005)
Whether you're a high school student looking for the latest info on your favorite rock group, or a seasoned attorney researching an old case, you're probably using Google. It seems like everyone is. And who can blame them? With access to more than three million documents in over 30 languages, Google is a researcher's dream. It's no wonder, then, that nearly 150 million Google searches are conducted each day. As a result, people are hungry to learn new ways to maximize its usefulness. Truth is, there are dozens upon dozens of techniques to learn--each designed to make your Google search more time-efficient, more productive, and more fun. And Google Hacks , Second Edition has the inside scoop on them all. An absolute must-have guide for anyone who searches the Internet--and these days that's just about everybody-- Google Hacks , Second Edition takes its best-selling predecessor one step further. In plain language, Google Hacks , Second Edition is an updated collection of industrial-strength, real-world tested solutions to practical research problems. Best of all, each of its 100 hacks are easy to read and digest--no confusing terminology or extraneous information to hamper your understanding. And although they can be read in just a few short minutes, when put to use, they can easily save you hours of research time. Now that's bang for your buck!